Outlook on the Brazilian scenario of floating photovoltaic solar energy - Domisley Dutra Silva; Elaine Maria Cardoso; Cláudio Basquerotto; João Antonio Pereira; Antonio Eduardo Turra; Jhonny Feldhaus (Energy Reports, 2023)
Brazil offers significant potential for installing floating photovoltaic systems in artificial reservoirs, as it represents the world's second-largest installed hydroelectric capacity, corresponding to 56.8% of the Brazilian electrical energy matrix. The current paper highlights the potential contributions of floating photovoltaic solar energy to the Brazilian renewable energy matrix, specifically regarding land use efficiency and water resource management. In addition, through a comparative analysis with a global scenario, this work shows the importance of Brazil's water bodies and sunlight for renewable energy generation. It shows that using 1% of surface areas in artificial water bodies in Brazil can generate 57,384 GWh/year, reaching up to 5 times the generation capacity, as indicated by more recent studies. Moreover, analyzing data for one-day hourly generation considering a hybrid system would result in an increase of approximately 4% in electricity generation. By leveraging its favorable conditions and addressing the challenges, Brazil has the opportunity to establish itself as a pioneer in the (FPV) sector, contributing to its sustainable energy future and the global transition to renewable sources.